Dissociable effects of prediction and integration during language comprehension: evidence from a large-scale study using brain potentials. (16th December 2019) - Nieuwland, Mante S.; Barr, Dale J.; Bartolozzi, Federica; Busch-Moreno, Simon; Darley, Emily; Donaldson, David I.; Ferguson, Heather J.; Fu, Xiao; Heyselaar, Evelien; Huettig, Falk; Matthew Husband, E.; Ito, Aine; et al.
Abstract : Composing sentence meaning is easier for predictable words than for unpredictable words. Are predictable words genuinely predicted, or simply more plausible and therefore easier to integrate with sentence context? We addressed this persistent and fundamental question using data from a recent, large-scale ( n = 334) replication study, by investigating the effects of word predictability and sentence plausibility on the N400, the brain's electrophysiological index of semantic processing. A spatio-temporally fine-grained mixed-effect multiple regression analysis revealed overlapping effects of predictability and plausibility on the N400, albeit with distinct spatio-temporal profiles. Our results challenge the view that the predictability-dependent N400 reflects the effects of either prediction or integration, and suggest that semantic facilitation of predictable words arises from a cascade of processes that activate and integrate word meaning with context into a sentence-level meaning. This article is part of the theme issue 'Towards mechanistic models of meaning composition'.